A Catheter-related Bloodstream Infection With Mycobacterium frederiksbergense in an Immunocompromised Child. Issue 4 (April 2015) - Senozan, Erin A.; Adams, Daniel J.; Giamanco, Nicole M.; Warwick, Anne B.; Eberly, Matthew D.
Abstract : We report a case of a catheter-related bloodstream infection with Mycobacterium frederiksbergense in an immunocompromised child with acute lymphoblastic leukemia. Nontuberculous mycobacteria have been implicated in central venous catheter infections in immunosuppressed individuals, however, to our knowledge this is the first reported case of invasive infection with this organism.